Duty of Care, Safety, Normalisation and the Mental Capacity Act: A Discourse Analysis of Staff Arguments about Facilitating Choices for People with Learning Disabilities in UK Services. (8th July 2014) - Jingree, Treena
Abstract: The benefits of having choice and control for people with learning disabilities1 are well documented, and front‐line carers often make efforts ensuring that these are facilitated. However, despite this, government policy reports that disempowerment within learning disability services in the UK is a persistent problem. Using critical discursive psychology, 15 interviews with support workers about empowering people with learning disabilities were analysed. Interpretative repertoires about 'duty of care', 'safety' and 'normalisation' and discursive strategies involving 'comparative evaluations' were found, which opened speaker positions of granting or withholding choice, assuming responsibility for those in care and constructing service users as lacking capacity. These resources also allowed speakers to regulate the choices of service users and to normalise limited choice in ways that undermined taking up more empowering practices. The findings may explain the persistence of disempowerment within services by indicating how such discourses are deeply entrenched in service talk and are invoked to justify disempowering practices. This is discussed in view of the implications for empowerment and also current legislative frameworks such as the Mental Capacity Act. Copyright © 2014 John Wiley & Sons, Ltd.